Custom and the 1962 Roman Missal: Canon 23 - Brown, Michel (CLSA advisory opinions, 2001-2005, 2003)
A few years ago, an opinion appeared in CLSA Advisory Opinions in which the author presented an opinion in which he addressed various errors vis-à-vis the use of the 1962 Roman Missal. One of these errors was the claim that every priest has a right, owing to immemorial custom, to celebrate Mass according to the 1962 liturgical books. As this erroneous view of custom has only become more popular among certain lay groups since then, could you please expand upon this earlier advisory opinion and address new erroneous opinions that have arisen concerning this issue since the publication of his advisory opinion?